Penegakan Hukum Pemberantasan Tindak Pidana Korupsi Pasca Putusan Mahkamah Konstitusi Nomor 25/PUU-XIV/2016 - Rio Rinaldi Silalahi (Lex Renaissance, 2018)
This study aims to determine the perspectives of Advocates and Corruption Eradication Commission (KPK) on the decision of the Constitutional Court (MK) No. 25/PUU-XIV/2016 concerning the removal of the word “can”; and how the law enforcement practices were carried out by Advocates and KPK after the Constitutional Court's decision. This research is normative with an empirical dimension and a juridical approach. The method used in analyzing the data is qualitative. The results show that, the perspective of the post-verdict advocate MK No. 25/PUU-XIV/2016 namely the change in formal offense to material offense is considered to provide fairer legal certainty. While the KPK's perspective on the decision was considered counterproductive in an effort to prevent state financial losses due to corruption. The implication is that the KPK is increasingly difficult to ensnare criminal acts of corruption from the natural resource or environmental sector that are potentially detrimental to state finances. Law enforcement practices carried out by lawyers after the Constitutional Court's decision have not been fully optimal. While the law enforcement practices carried out by the KPK after the Constitutional Court's ruling are as usual because before the Constitutional Court's ruling, the KPK always bases state financial losses with certainty, even if they create potential state losses, also attaching certainty (Both).